2004
DOI: 10.1161/01.res.0000124761.62846.df
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That IGF Binding Protein-5 Functions as a Ligand-Independent Transcriptional Regulator in Vascular Smooth Muscle Cells

Abstract: Abstract-Insulin-like growth factor binding protein (IGFBP)-5 is a conserved protein synthesized and secreted by vascular smooth muscle cells (VSMCs). IGFBP-5 binds to extracellular IGFs and modulates IGF actions in regulating VSMC proliferation, migration, and survival. IGFBP-5 also stimulates VSMC migration through an IGF-independent mechanism, but the molecular basis underlying this ligand-independent action is unknown. In this study, we show that endogenous IGFBP-5 or transiently expressed IGFBP-5-EGFP, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
93
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 46 publications
3
93
0
Order By: Relevance
“…It has also been reported that IGFBP-5 may interact with Four and a Half LIM protein 2 (FHL2) and retinoid X receptor, nuclear proteins known to be involved in transcriptional regulation (16,17). Recently, we have shown that 1) endogenous IGFBP-5 is localized in the nucleus of cultured porcine vascular smooth muscle cells; 2) several basic residues in the IGFBP-5 C-domain are necessary and sufficient for nuclear localization of the intact protein; and 3) the IGFBP-5 N-domain activates transcription independent of IGF (18). These findings suggest that IGFBP-5 is present in the nucleus and may affect gene expression independent of the IGF ligand.…”
mentioning
confidence: 99%
“…It has also been reported that IGFBP-5 may interact with Four and a Half LIM protein 2 (FHL2) and retinoid X receptor, nuclear proteins known to be involved in transcriptional regulation (16,17). Recently, we have shown that 1) endogenous IGFBP-5 is localized in the nucleus of cultured porcine vascular smooth muscle cells; 2) several basic residues in the IGFBP-5 C-domain are necessary and sufficient for nuclear localization of the intact protein; and 3) the IGFBP-5 N-domain activates transcription independent of IGF (18). These findings suggest that IGFBP-5 is present in the nucleus and may affect gene expression independent of the IGF ligand.…”
mentioning
confidence: 99%
“…Loss of FLNa is associated with a loss of IGFBP-5-mediated induction of lamc1 transcription, thereby establishing the functional significance of these findings. Previous studies have indicated that IGF-1-independent effects of IGFBP-5 are mediated through intranuclear effects on transcription (9,13,18), yet details of those effects have not been elucidated. Similarly, intranuclear effects of FLNa that modulate effects of transcription factors on target genes have not been thoroughly defined.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first demonstration of the interaction of IGFBP-5 with FLNa both in the cytosol and nucleus of IGFBP-5-treated cells. Additional studies are required to determine whether IGFBP-5 is directly mediating FLNa import into the nucleus or whether it has accessory effects on transcription (9,13).…”
Section: Igfbp-5 Induces Flna Binding and Nuclear Translocation Of Trmentioning
confidence: 99%
See 2 more Smart Citations